Pemanfaatan Youtube Sebagai Sarana Transformasi Majalah Highend - Yolanda Stellarosa; Sandra Jasmine Firyal; Andre Ikhsano (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
The emergence of a variety of social media makes it easier for people to find and obtain information. One of the social media that can provide information in the form of audio and visual without any duration limit is YouTube.YouTube HighEnd Magazine is HighEnd magazine's YouTube channel used as a transformation tool for the magazine. This research uses descriptive qualitative method. The purpose of this study is to determine the utilization of social media YouTube as a tool of transformation of HighEnd magazine. Researcher interviewed three different speakers that have different job desks, Larasati Oetomo as digital media officer, Lysia Jessica as editor in chief, and Johan Jang as social media expert. This research uses new media theory and describes media utilization strategies to find out how Highend magazine utilizes YouTube’s social media. This research proves that HighEnd has utilized YouTube social media with six characteristics of New Media as a means of transformation of print media, has also developed strategies in utilizing YouTube based on Audience, Mission, Goal, and Content Strategy.